2019
DOI: 10.1111/josh.12715
|View full text |Cite
|
Sign up to set email alerts
|

All Things in Moderation? Threshold Effects in Adolescent Extracurricular Participation Intensity and Behavioral Problems

Abstract: BACKGROUND: School-based extracurricular activity participation is one of the primary avenues for prosocial activity engagement during adolescence. In this study, we test the “overscheduling hypothesis” or whether the negative relationship between structured activity intensity (ie, hours) and adolescent bullying and fighting levels off or declines at moderate to high intensity (ie, threshold effects). METHODS: This study uses the Dane County Youth Survey (N = 14,124) to investigate the relationship between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…This finding aligns with other findings that bullying is most often experienced by students who either participate in no extracurricular activity or participate in 5 or more hours per week of extracurricular activity. 23 Further research is needed, including longitudinal studies before and after a school transitions to a 4-day week, to learn how the schedule change affects adolescent health-related behaviors and how time is spent on the off day. Future research could also explore to what extent schools or other organizations in the community offer activities on the days previously spent in school.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with other findings that bullying is most often experienced by students who either participate in no extracurricular activity or participate in 5 or more hours per week of extracurricular activity. 23 Further research is needed, including longitudinal studies before and after a school transitions to a 4-day week, to learn how the schedule change affects adolescent health-related behaviors and how time is spent on the off day. Future research could also explore to what extent schools or other organizations in the community offer activities on the days previously spent in school.…”
Section: Discussionmentioning
confidence: 99%
“…These suggest a possible beneficial impact on mental health such as behavioral outcomes, self-esteem and self-confidence ( Bungay and Vella-Burrows, 2013 , Zarobe and Bungay, 2017 ). Contrary, some studies have observed harmful consequences of organized activities, such as risk behavior and bullying( Badura et al, 2017 , Fredricks and Eccles, 2008 , Matjasko et al, 2019 , Randall and Bohnert, 2012 ) In two of these studies this depended on the amount of time that was spend in the organized activities( Matjasko et al, 2019 , Randall and Bohnert, 2012 ) ()…”
Section: Introductionmentioning
confidence: 99%
“…Sport and other forms of active and voluntary social participation can be a means for adolescent development. Previous research shows that male and female youth engagement in sport can reduce the likelihood of aggressive and violent behaviors [4] and promote adolescent physical and mental health through improved fitness levels [5À8] and via positive and collaborative peer engagement [7]. These effects may be driven by sport supporting positive youth development through the pathways of building self-esteem, collaboration, and kinship [9].…”
Section: Introductionmentioning
confidence: 99%